The social sustainability of multicultural cities: a neighbourhood affair? - Annick Germain (Belgeo)
In multiethnic cities sustainable social development partly depends on the coexistence of social and cultural differences and on the diversity management policies. Several researches directed by the author on Montreal’s multiethnic neighbourhoods show to what extent the neighbourhood remains an ideal laboratory for understanding how those modes of coexistence develop. One should however avoid basing all forms of intervention in the field of diversity management on a concept of the neighbourhood-as-village which does not correspond with the urbanity of some social practices, at least in a metropolitan city like Montreal.